La gestión del talento humano y su incidencia en el desempeño laboral en el Gobierno Autónomo Descentralizado Municipal del cantón San Jacinto de Buena Fe, año 2015. - Briones Zambrano, Digna Antonieta (2015)
The talent management is very important and should be well oriented organizations; we must remember that this should result in employees a great satisfaction. It is considered that the human talent within the organization should be trained to become highly competitive people ready to take on major organizational challenges, this must happen through the correct steps in charge of human talent manager, who is responsible for ensure the welfare of its staff and efficiency in the administration of the institution. This research was performed in order to check how human talent management functions within the Decentralized Autonomous Government of the Canton San Jacinto de Buena Fe and this affect job performance. By applying techniques of data collection were the application of interviews and surveys of staff and director of human talent, it was found that the current profiles in the organization are not defined, there is no right talent management, there shortcomings in training programs and practices to measure lacks control parameters by defining tools. After the investigation the results of research evidence, such as through the implementation of the key factors SWOT weaknesses and threats for the organization promoting this constant control on those points that pose a risk to the organization was determined, was evident that good management of human talent that allows encourage good stewardship of resources, and finally propose strategies intended to serve as guidance to staff and bosses and managers in the organization, after obtaining necessary results are applicable to provide conclusions and recommendations to senior management and an alternative proposed as a solution to the problem that exists in the organization which consists in creating motivation strategies for obtaining a high level of job satisfaction for employees in the organization intends.